A History of Cambodia - Chandler, David (Silkworm books, 1993)
This acclaimed text has now been completely revised and updated to include material examining the early history of Cambodia, whose famous Angkorean ruins now attract more than one million tourists each year, the death of Pol Pot, and the revolution and final collapse of the Khmer Rouge. The fourth edition reflects recent research by major scholars as well as Chandler's long immersion in the subject and contains an entirely new section on the challenges facing Cambodia today, including an analysis of the current state of politics and sociology and the increasing pressures of globalization. This comprehensive overview of Cambodia will illuminate, for undergraduate students as well as general readers, the history and contemporary politics of a country long misunderstood.